2006
DOI: 10.1021/jf061699g
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Atrazine and Cadmium from Soil by Maize (Zea mays L.) in Association with the Arbuscular Mycorrhizal Fungus Glomus etunicatum

Abstract: A greenhouse pot experiment was carried out to investigate the effect of the arbuscular mycorrhizal fungus Glomus etunicatum on the uptake of atrazine (ATR) and cadmium (Cd) from soil by maize (Zea mays L.). Mycorrhizal colonization led to an increase in the accumulation of Cd and ATR in maize roots but a decrease in the shoots. Atrazine alleviated the adverse effects of Cd on maize growth, and this was more pronounced in the inoculated plants. An increase in Cd accumulation by maize roots was observed when AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 22 publications
3
7
0
1
Order By: Relevance
“…There was a significant decrease in the residual atrazine concentration in the soil after plant harvest (P < 0.05) and this became more evident with inoculation, which was consistent with our previous findings for atrazine by bulk cultivation (Huang et al, 2006). Atrazine in soil decreased more in the extraradical mycelium compartment than in the mycorrhizal root compartment when the atrazine addition rate to soil was 5.0 mg kg À1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There was a significant decrease in the residual atrazine concentration in the soil after plant harvest (P < 0.05) and this became more evident with inoculation, which was consistent with our previous findings for atrazine by bulk cultivation (Huang et al, 2006). Atrazine in soil decreased more in the extraradical mycelium compartment than in the mycorrhizal root compartment when the atrazine addition rate to soil was 5.0 mg kg À1 .…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that in rhizosphere soil atrazine degradation is associated with higher dehydrogenase (Seibert et al, 1991;Singh et al, 2004) and phosphatase activities (Perucei et al, 1988;Bielinska and Pranagal, 2007), and atrazine can influence the populations of certain microbial groups (Ros et al, 2006). We observed in our previous studies that atrazine dissipation in soil was enhanced by AM inoculation (Huang et al, 2006). We therefore hypothesized that increased dissipation of atrazine in soil might contribute to: (1) specific effects of mycorrhizal roots and extraradical mycelium on atrazine dissipation; and/or (2) modification of the effects on soil enzyme activities and microbial community structure resulting from mycorrhizal inoculation.…”
Section: Introductionsupporting
confidence: 52%
“…Unlike other pesticides, the herbicide atrazine at lower concentration decreases mycorrhizal colonization, whereas at higher concentration, it stimulates colonization (Huang et al 2006(Huang et al , 2007. However, it has been speculated that the application of higher concentrations of atrazine tends to induce tolerance in AM fungi, although the real mechanism behind the varied effect is yet to be elucidated (Huang et al 2007 ).…”
Section: Biocidesmentioning
confidence: 99%
“…Pot experiments demonstrated that dual inoculation of M. sativa with G. versiforme or G. caledonium and Rhizobium meliloti achieved the most efficient removal of polychlorinated biphenyls from contaminated soils [201,202]. Atrazine accumulation was shown to decrease in maize shoots but increase in roots when the plant was associated with Glomus etunicatum [203,204]. More atrazine metabolites, deethylatrazine and deisopropylatrazine, were metabolized in AM-maize roots, leading to atrazine dissipation in the rhizosphere and bulk soils [204].…”
Section: Potential Of Am Fungi In Phytoremediation And/or Land Reclammentioning
confidence: 99%